Blood values observed in some breeds of cattle in the savanna regions of Nigeria - Wood, A.S.; Kramer, J.W. (1968)
Blood was obtained from cattle representing the white Fulani, N’Dama, Muturu and Holstein-Friesian breeds and was collected during the period June 1965 to April 1966. The age group represented ranged from 2 to 11 years and included both males and females. Haemoglobin content, packed cell volume and red blood cell count were recorded for all the breed types mentioned in the study. Haemoglobin content of Holstein Friesian, N’Dama, Muturu and white Fulani were 9.50, 15.20, 13.70 and 10.60 mg/100ml respectively. Packed cell volume percentage was 28.65, 36.00, 36.20 and 26.60 white mean corpuscular haemoglobin concentration (McHc) were 33.20, 42.20, 37.80 and 36.20 respectively.